Successful unconventional precision treatment of inflammatory hormone receptor-positive breast cancer guided by molecular profiling - Jailan Elayoubi; Yu Zong; Erich J. Schwartz (npj Precision Oncology)
Abstract We present a unique case of locally advanced, inflammatory hormone receptor (HR) positive, human epidermal growth factor receptor 2 (HER2)-negative breast cancer in a young woman. A MammaPrint gene signature performed on the core biopsy indicated a very high risk of recurrence (MammaPrint high risk 2, MPH2). BluePrint 80-gene signature was used for the molecular subtyping and identified the tumor as a basal subtype, resembling triple-negative breast cancer (TNBC) despite the strong estrogen receptor (ER) expression on immunohistochemical (IHC) staining. We treated the patient with a TNBC protocol, incorporating carboplatin and immunotherapy into the anthracycline-based chemotherapy backbone in the neoadjuvant setting. The patient achieved a complete response and remains to be disease-free after 2 years, with ongoing follow-up.